The use of digital storytelling in the teaching of reading at a rural primary school - Ramalepe, Matome Liphy; Westhuizen, Gert Van der (International Journal of Educational Technology and Learning, 2024)
The myriad challenges confronting schools have stimulated proposals to adopt digital storytelling as both an innovative teaching strategy and learning resource. Due to inadequacy in reading skills of our school learners, language teachers have acceded to a proposal to use digital storytelling as a vehicle for curriculum delivery. Therefore, the purpose of this study is to examine the perceptions of the rural primary school teachers regarding the use of digital storytelling in the teaching of reading. To do so, the researcher employed a three-cyclical process of qualitative action research which involved pre-implementation, implementation and post-implementation stages. To gather data from five language teachers, interviews were used during pre-implementation phase, observations were conducted during the implementation phase, and document analysis and interviews were employed during the post-implementation phase. Results show that the teachers’ readiness levels in terms of technological skills, beliefs and attitude improved after attending the Digital Storytelling Workshop. The notable end-product of the Digital Storytelling Workshop was three digital stories that teachers developed by teachers. In sum, teachers demonstrated an adequate degree of readiness to adopt digital storytelling after the post-implementation phase. The positive outcomes of this action research study suggest that digital storytelling should be used as an innovative strategy to teach reading.